Common Ownership and Market Entry: Evidence from the Pharmaceutical Industry - Melissa Newham; Jo Seldeslachts; Albert Banal-Esta\~nol (Deutsches Institut für Wirtschaftsforschung (DIW), 2022)
Common ownership - where several firms are (partially) owned by the same investors - and its impact on product market competition has recently drawn much attention. This paper focuses on its implications for market entry. Specifically, we consider the entry decisions of generic pharmaceutical firms into drug markets that are opened up by the end of regulatory protection and which were previously dominated by a single firm selling the brand name drug. We find evidence that common ownership affects entry in US pharmaceutical markets. In particular, we find that an increase in common ownership leads to a reduction in entry, both at the individual and market level. This key finding is robust to different measures of common ownership, different sets of potential entrants, different estimation methods and specifications, different market definitions, and different outcome variables.
Keywords: G23; K21; L11; L41; L65; 330; Market Entry; Ownership Structure; Pharma